2019
DOI: 10.1002/ijc.32495
|View full text |Cite
|
Sign up to set email alerts
|

The topology of vitronectin: A complementary feature for neuroblastoma risk classification based on computer‐aided detection

Abstract: Tumors are complex networks of constantly interacting elements: tumor cells, stromal cells, immune and stem cells, blood/lympathic vessels, nerve fibers and extracellular matrix components. These elements can influence their microenvironment through mechanical and physical signals to promote tumor cell growth. To get a better understanding of tumor biology, cooperation between multidisciplinary fields is needed. Diverse mathematic computations and algorithms have been designed to find prognostic targets and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Both niches, which initially lacked VN, showed a large amount of VN secreted by neuroblats [22]. Our results show new evidence for the probably role of VN in biotensegrity mechanotransduction by mediating the cellular response to ECM stiffness [22,56]. The adaptation process was faster in VN-KO tumor cells but less manageable than in hydrogels.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Both niches, which initially lacked VN, showed a large amount of VN secreted by neuroblats [22]. Our results show new evidence for the probably role of VN in biotensegrity mechanotransduction by mediating the cellular response to ECM stiffness [22,56]. The adaptation process was faster in VN-KO tumor cells but less manageable than in hydrogels.…”
Section: Discussionmentioning
confidence: 59%
“…In previous studies, we demonstrated that elevated VN secretion by tumor cells was founded in rigid ECMs, and was related to poor patient outcomes and to growth of orthotopically inoculated NB cell lines [22]. Moreover, we observed that the high amount of VN is secreted forming tracks and we postulated that VN participates in stiffness, mediating biotensegrity and promoting tumor migration in HR-NB [22,56]. We also reported that SK-N-BE(2) cells grown in stiff 3D hydrogels show more e cient adaptation, increased cell proliferation, high expression of the Bcl2 antiapoptosis marker, and high mRNA processing rate (24).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…NB stiff ECM is rich in cross-linked collagen III bers, poor in glycosaminoglycans, supporting sinusoidal vascular structures (blood and lymphatic) and with a high quantity of territorial vitronectin (VN, located in the cytoplasmic compartment and in a thin layer around the tumor cells) [19][20][21][22]. NB stiff ECM is also rich in collagen I bers and bronectin but in lesser amounts and with a more physiologicallike topology than collagen III and VN [18,23] Moreover, VN is a glycoprotein containing multiple cell receptor binding sites including integrins, uPAR and PAI-1 [24], and which can therefore form transitory ECM element-cell junctions. It seems to anchor to ECM bers and proteoglycans, and also disrupt cell adhesion, promoting spread and metastasis in NB [22,25].…”
Section: Introductionmentioning
confidence: 99%